Functional and clinical evaluation of renal injury in patients treated with adjuvant chemoradiotherapy for gastric cancer: Low dose and comorbidity considerations - ATASOY, BESTE MELEK; DANE, FAYSAL; DEDE, FUAT; ARIKAN, İZZET HAKKI (ELSEVIER SCIENCE BV, 2016)
Aim: To analyze the dosimetric factors affecting long-term renal function in patients with gastric cancer following postoperative radiotherapy with concomitant chemotherapy to the upper abdomen. Methods: Between January 2005 and July 2010, 13 patients treated with three-dimensional conformal radiotherapy and concurrent fluorouracil-based chemotherapy (CRT) were included in this analysis. After a median follow-up of 55 months, creatinine, glomerular filtration rate (GFR), total kidney and left kidney volumes, before and after CRT and mercaptoacetyltriglycine (MAG3) scintigraphy, were used to evaluate the renal function and were correlated with the dosimetrics data. Results: Significant correlations were found in the loss of left kidney volume and V35 (20.6%) (p = 0.035) and V40 (15.7%) (p = 0.031) and in the loss of relative functional contribution of the main kidney and V35 Gy (p = 0.027) and V40 Gy (p = 0.019). In patients with a slightly low basal GFR (n = 6), the relative functional contribution of the left kidney significantly decreased, regardless of the dosage. Conclusion: Functional renal impairment without any clinical signs or symptoms can be observed in low doses after radiotherapy. Careful treatment planning and a detailed evaluation of the functional renal capacity before treatment may help to reduce late renal toxicity. Copyright (C) 2015, The Egyptian Society of Radiation Sciences and Applications. Production and hosting by Elsevier B.V.
Keywords: Comorbidity; Dose volume effect; Late effect; Radiotherapy; Renal toxicity; RADIATION NEPHROPATHY; NORMAL TISSUE; IRRADIATION; TOXICITY; CISPLATIN; TOLERANCE